The Effect of Robotics Experiments on the Scientific Literacy of Junior High School Students in Bengkulu Province - Mayub, A.; Setiawan, A.; Fahmizal, F.; Wardaya, R. W.; Lazfihma, L; Johan, H.; Nursaadah, E. (Jurnal Pendidikan IPA Indonesia, 2023)
This research describes students' scientific literacy, motivation to learn science, and science teachers' responses after participating in the "Robotic Experiment." The research uses experimental methods, which include interactive lectures, demonstrations, simulations, question and answer, animations, and robot assembly. Research data was obtained using questionnaires and interviews with 100 students and 25 science teachers from SMP N 6 Seluma, SMP N 2 Bengkulu, SMP N 8 Rejang Lebong, SMP N 2 Kepahiyang, and SMP N 4 Rejang Lebong. The school prepared a simple electronics/robot laboratory for the five research subjects in this research activity. Robotics experiments can motivate students at junior high schools in Bengkulu to learn science, increase students' scientific literacy, and science teachers' responses to the experiment, each with a score of 4.02 (motivated category), 3.99 (good category), and 3.98 (good response category). The school aims to pursue this robotics experiment further in the future to stimulate students' curiosity about science learning inside and outside the classroom.